2017
DOI: 10.1111/cote.12287
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of tannin‐impregnated and varnished beech wood after exposure to accelerated weathering

Abstract: The aim of this study was to determine selected surface properties of varnished beech wood impregnated with natural extracts after exposure to accelerated weathering. Beech wood samples were impregnated with aqueous solutions of 5 and 10% mimosa (Acacia mollissima) and quebracho (Shinopsis lorentzii) tannins. After weathering, colour changes (DL*, Da*, Db*, and DE*) in addition to scratch resistance and surface hardness values were calculated and evaluated. As a result of the weathering process, greater colour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
(54 reference statements)
0
12
0
1
Order By: Relevance
“…After accelerated weathering, in terms of varnish type, the lowest colour change values were obtained with PV, followed by water‐based varnish and then CV. The authors also reported that PV had highest surface hardness, followed by water‐based and cellulosic coatings . Improving the durability and surface performance of wood with various applications for weathering conditions is important for its value.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…After accelerated weathering, in terms of varnish type, the lowest colour change values were obtained with PV, followed by water‐based varnish and then CV. The authors also reported that PV had highest surface hardness, followed by water‐based and cellulosic coatings . Improving the durability and surface performance of wood with various applications for weathering conditions is important for its value.…”
Section: Introductionmentioning
confidence: 94%
“…Yalcin et al 14 investigated the surface properties of Oriental beech wood samples treated with tannins and TN-E before PV, water-based varnish and cellulosic varnish (CV) after accelerated weathering. The authors found that total colour changes increased in both the control specimens and the impregnated specimens exposed to weathering periods ranging from 100 to 300 hours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results are variable, but the use of a combination of UV-stabilizers and HALS [ 10 , 42 ] and TiO 2 or ZnO nanoparticles [ 49 , 50 , 51 ] seems to be the most effective. In addition, it is necessary to consider the fact that the kind of underlying wood species, and in particular the content of specific extractives [ 52 ], significantly affects the reaction to the impacting UV radiation [ 53 , 54 , 55 ] and also reacts differently with the additives and polymeric foundations contained in the coatings [ 4 , 33 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Le vieillissement artificiel ou accéléré influe sur la couleur du bois traité ou non traité par finition [12][13][14][15][16][17][18][19].…”
Section: Introductionunclassified